Online Motorcycle Taxi Services and Smartphone Use while Driving - Nurani Eka Saputri; Mutimatun Niami (Universitas Muhammadiyah Surakarta, 2024)
The use of smart phones by online motorcycle taxi services drivers while driving brings complex impacts, including the risk of traffic accidents, vio lations of the law, and liability in accident cases. The main problem that arises is the extent of legal protection available to online motorcycle taxi services drivers who use smart phones while driving and how existing regulations address this challenge. This study aims to examine the legal protection of online motorcycle taxi services drivers who use smart phones while driving. This research method uses juridical normative to relevant legal provisions. The results showed that the need for clearer and str icter regulations to protect the rights and welfare of online motorcycle taxi services drivers. In addition, the need for concrete steps from related parties to improve legal protection for online motorcycle taxi services drivers who use smart phones while driving.